2008
DOI: 10.1016/j.cellbi.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution of spermidine/spermine N1‐acetyltransferase

Abstract: The subcellular distribution of the polyamine catabolic enzyme spermidine/spermine N(1)-acetyltransferase (SSAT) was studied in L56Br-C1 cells treated with 10 microM N(1),N(11)-diethylnorspermine (DENSPM) for 24 h. Cells were fractioned into three subcellular fractions. A particulate fraction containing the mitochondria was denoted as the mitochondrial fraction. After DENSPM treatment, an increase in SSAT activity was mainly found in the mitochondrial fraction. Western blot analysis showed an increased level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The uptake of JC-1 is dependent on the mitochondrial transmembrane potential [39]. We have seen the same phenomenon using another mitochondrial stain [50]. Our data point to a polyamine analogue-induced increase in mitochondrial respiration, thus supporting the notion that DC m is increased in DENSPM-treated cells [11,26].…”
Section: Discussionsupporting
confidence: 84%
“…The uptake of JC-1 is dependent on the mitochondrial transmembrane potential [39]. We have seen the same phenomenon using another mitochondrial stain [50]. Our data point to a polyamine analogue-induced increase in mitochondrial respiration, thus supporting the notion that DC m is increased in DENSPM-treated cells [11,26].…”
Section: Discussionsupporting
confidence: 84%
“…SSAT is generally considered to be predominantly cytosolic, but a recent study indicated a mitochondrial location for a large portion of the SSAT after induction by BE-3-3-3 in a breast cancer cell line (62). It has also been reported that SSAT is phosphorylated by casein kinase-1 and -2 and that this affects binding to mitochondrial membranes (17).…”
mentioning
confidence: 97%
“…Under DENSpm-induced conditions, using immunohistochemistry and immunocytochemistry, SSAT has been detected in the cytoplasm of human adenocarcinoma A549 cells and in the cytoplasm, nucleus and mitochondria of human breast cancer L56Br-C1 cells respectively [23,24]. We were not able to detect the SSAT–EGFP under the fluorescent microscope unless DENSpm or CPENSpm was added to the growth medium.…”
Section: Discussionmentioning
confidence: 95%